Noise Trauma Induced Neural Plasticity Throughout the Auditory System of Mongolian Gerbils: Differences between Tinnitus Developing and Non-Developing Animals - Tziridis, Konstantin; Ahlf, Sönke; Jeschke, Marcus; Happel, Max F. K.; Ohl, Frank W.; Schulze, Holger (Frontiers in Neurology, 2015)
In this study, we describe differences between neural plasticity in auditory cortex (AC) of animals that developed subjective tinnitus (group T) after noise induced hearing loss (NIHL) compared to those that did not (group NT). To this end, our analysis focuses on the input activity of cortical neurons based on the temporal and spectral analysis of local field potential recordings (LFP) and an in-depth analysis of auditory brainstem responses (ABR) in the same animals. In response to NIHL in NT animals we find a significant general reduction in overall cortical activity and spectral power as well as changes in all ABR wave amplitudes as a function of loudness. In contrast, T animals show no significant change in overall cortical activity as assessed by root mean square analysis of LFP amplitudes, but a specific increase in LFP spectral power and in the amplitude of ABR wave V reflecting activity in the inferior colliculus (IC). Based on these results we put forward a refined model of tinnitus prevention after NIHL that acts via a top-down global (i.e. frequency-unspecific) inhibition reducing overall neuronal activity in AC and IC, thereby counteracting NIHL induced bottom-up frequency-specific neuroplasticity suggested in current models of tinnitus development.